Association between admission serum phosphate and risk of acute kidney injury in critically ill patients with rhabdomyolysis: A retrospective study based on MIMIC-Ⅲ. Issue 1 (January 2023) - Wen, Tao; Mao, Zhi; Liu, Chao; Wang, Xiaoli; Tian, Shufen; Zhou, Feihu
Abstract: Background: The incidence of acute kidney injury (AKI) is high in critically ill patients with rhabdomyolysis. Limited evidence was proved of the association between serum phosphate levels at intensive care unit (ICU) admission and the subsequent risk of AKI. Our study aims to assess if serum phosphate levels at admission were independently associated with AKI risk in these patients. Methods: This study extracted and analyzed data from Medical Information Mart for Intensive Care-Ⅲ (MIMIC-Ⅲ, version1.4). Rhabdomyolysis was defined as a peak creatine kinase (CK) level higher than 1000 U/L. Serum phosphate was measured within the first day into the ICU and was categorized to 4 groups (<2.6, 2.6-3.4, 3.5-4.5, >4.5mg/dl). AKI was defined according to the Kidney Disease Improving Global Outcome (KDIGO) guidelines. Adjusted smoothing spline plots and multivariable logistic regressions were carried out to explode the association between serum phosphate and risk of AKI. Subgroup analyse was applied to verify the consistency of the association. Results: Three hundred and twenty-one patients (68% male) diagnosed as rhabdomyolysis were eligible for this analysis. AKI occurred in 204 (64%) patients of total. Incidence of AKI with admission serum phosphate groups<2.6, 2.6-3.4, 3.5-4.5 and>4.5mg/dl were 53%, 57%, 68% and 76%, respectively. Smoothing spline curve showed that there was a positive curve between the elevated phosphate values and increasing risk of AKI, and there was no threshold saturation effect. In multivariable logistic regression, OR was 1.2 (95%CI 1.0-1.5, P=0.035, P trend=0.041) after adjusting confounders. Subgroup analyses proved the consistency of the relationship in these patients, possibly, except in the strata of potassium. Conclusion: In rhabdomyolysis patients admitted to ICU, serum phosphate levels at admission were independently associated with an increased risk of AKI. As phosphate levels rise, the risk of AKI increased.